A REVIEW ARTICLE: ANTIOXIDANT ACTIVITY IN KALAKAI (Stenochlaena palustris): ARTIKEL REVIEW: AKTIVITAS ANTIOKSIDAN PADA KALAKAI (Stenochlaena palustris) - Oksal, Efriyana; Ayuchecaria, Noverda; Agnestisia, Retno; Ariska, Risya; Tampubolon, Mulani Jeni Lestari; Dewi, Sintia Ayu; Maulana, Ilham; Rizkita, Aden Dhana (ALOTROP, 2023)
Kalakai (scientific name Stenochlaena palustris) is a type of fern that is often used by the people of Kalimantan as a vegetable. The Kalakai plant which grows a lot in the lowland swamp areas of Central Kalimantan is a type of fern plant. Kalakai contains high levels of minerals, vitamin C, folic acid, and protein when compared to other local vegetables in Palangka Raya, Central Kalimantan. The active compounds that act as antioxidants in kalakai are flavonoids and phenols. Flavonoids and phenols act as free radical scavengers to prevent diseases that attack the body thereby strengthening the body's immunity. Traditionally, kalakai is consumed by the Dayak people. This article is a review article that uses the descriptive literature study method to find scientific information or research that proves coherently the benefits or applications of the kalakai. Kalakai which activity as an antioxidant has health benefits such as being able to increase hemoglobin levels so that it can prevent anemia has cytotoxicity in MCF-7 breast cancer cells and prevents antihyperlipidemic by reducing Low-density lipoprotein (LDL).